Massive traumatic events and posttraumatic stress disorder - YILDIZ, MESUT (NOVA Science Publishers Inc., 2021)
Posttraumatic stress disorder (PTSD) is a psychiatric disorder that mayoccur in people who have experienced or witnessed a traumatic event suchas a natural disaster, a serious accident, a terrorist act, war/combat, or rapeor who have been threatened with death, sexual violence, or serious injury.Individuals with PTSD may have impairments in aspects of theirpsychological, physical, interpersonal, and occupational lives. PTSDusually has a chronic course and causes disruptions in the general andsocial functioning of the person. PTSD can be both underdiagnosed andoverdiagnosed in clinical settings. There are clear differences in the clinicalapproach to PTSD cases and the forensic perspective. The medicolegalapproach is different from the clinical viewpoint. Psychiatrists arefrequently asked for evaluations of traumatic events in civil and criminalmatters. Psychiatrists are asked to evaluate if the traumatic event caused orcontributed to a psychiatric disorder or a functional impairment. They arealso asked to make a distinction between causal and contributing factors.In addition, the factors that contribute to the person’s current mental stateand functionality should be well reviewed, and a possible malingeringshould not be overlooked. This chapter will review the clinical and ethical implications in evaluating patients with PTSD in a forensic setting.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)